Evaluación de modelos aproximados para el diseño de control automático en sistemas de riego a canal abierto (2020)
The increase in the population and its dependence on agricultural production has increased exponentially throughout history. For this through land cultivation, agriculture satisfies the demand for food, however, in the process this activity requires millions of liters of water, which are distributed in open-channel irrigation systems. In Colombia, the lack of technological investment and the few studies lead to a lack of structures capable of avoiding and controlling water waste. This problem can be addressed from the automatic control of irrigation systems, which are developed from mathematical models approximately predict water dynamics, such as flow variations, system obstructions, discharges and water level along the channels. For this reason this project aims to evaluate models reported in the literature that have been used in the design of automatic control for irrigation channels, through a proposed channel of three sections, selecting the one that best suits the dynamics of SWMM software to apply it to a case study, from which it is determined that the adjustment of some approximate models is more appropriate than others, and that it is possible to continue to expand the research and development of models that are more precisely approaching the dynamics of water, in order to implement automatic control design strategies in irrigation systems to open channel in Colombia.